First Report of Fusarium luffae Causing Leaf Blight on Loquat in Eastern China - Zhang, Shiling; Wang, Bo; Cao, Ying; Ji, Yanping; Sun, Qing; Shi, Xinchi; Herrera-Balandrano, Daniela D; Laborda, Pedro (Plant disease, 2024)
During May-June 2021 and 2022, leaf blight symptoms were observed on loquat leaves (Eriobotrya japonica cv. 'Mogi') in Jiangsu Province (Xuzhou municipality, 117.17° E, 34.13° N) in China. Approximately 10% of the leaves on the two hundred trees studied in a six-year-old loquat orchard exhibited round lesions that changed from light yellow to reddish-brown in 8-10 days. Approximately 3% of the infected leaves exhibited numerous lesions that coalesced, leading to expansive blighted areas. Twenty-five samples of symptomatic tissue, approximately 0.2 cm2 in size, were collected in May 2022 from five different trees (five samples per tree), sterilized in 2% NaOCl for 1 min, washed twice with sterilized ddH2O, and incubated at 26°C for 5 days on PDA medium containing 50 µg/mL chloramphenicol. Six isolates were obtained via single spore isolation. ITS (OQ954852-OQ954857), TUB2 (OQ968488-OQ968493), EF1-α (OQ971890-OQ971895), RPB1 (OQ971896-OQ971901), and RPB2 (OR037266-OR037271) genes were amplified using the ITS1/ITS4, T1/T22, EF1-728F/EF1-986R, RPB1-R8/RPB1-F5, and fRPB2-7CF/fRPB2-11aR primers, respectively (O'Donnell et al. 2010). The species was identified using the Fusarioid ID database (Crous et al. 2021), revealing that all obtained isolates showed high homology to representative F. luffae strains. Upon combining the ITS, TUB2, EF1-α, RPB1, and RPB2 sequences, the isolates showed 99.42%-97.85% and 99.59%-98.10% identity to F. luffae CGMCC 3.19497 (ex-type strain) and NRRL 32522, respectively. A molecular phylogenetic tree was constructed using MEGA X, with a selection of representative Fusarium strains. Microscope observations showed septate mycelium, microconidia (6.86 ± 0.91 µm length, 1.67 ± 0.24 µm width, containing 1 septum; number of observations = 21), fusiform macroconidia (15.88 ± 1.43 µm length, 1.66 ± 0.24 µm width, containing 1 septum; number of observations = 45), and linear chlamydospores (79.36 ± 28.36 µm length, 12.03 ± 3.37 µm width; number of observations = 152). These observations are consistent with the morphology of F. luffae (Wang et al. 2019). All isolates exhibited identical morphological characteristics. All isolates were evaluated for pathogenicity in vivo using healthy non-detached loquat leaves. A total of 15 leaves from 5 different three-month-old 'Mogi' loquat trees were used for each isolate. Experiments were performed three times. A suspension of 1 × 106 spores/mL obtained from a seven-day-old colony (10 mL per 15 leaves), was sprayed on non-wounded leaves for inoculation. Sterilized ddH2O was used in the control experiment. Inoculated trees were stored at 26°C and 70% relative humidity for four days. Leaf blight symptoms were observed in all inoculated leaves, and the symptoms were observed in all repeated trials. The pathogen was recovered, and its identity was confirmed by ITS sequencing and morphological analysis, fulfilling Koch's postulates. In recent years, F. luffae has been reported to cause fruit rot on muskmelon, flower rot on kiwifruit, soybean pod rot, and leaf spot on cherry in China (Yu et al. 2022; Zhang et al. 2022; Zhao et al. 2022; Zhou et al. 2022), demonstrating the host promiscuity of this pathogen. Although F. solani has been identified as the causal agent of root rot and fruit rot on loquat (Abbas et al. 2017; Wu et al. 2021), this is the first report of F. luffae causing leaf blight on loquat worldwide. This report will help to understand the pathogens affecting loquat orchards in China.